Post-crystallization alteration of natural uraninites: Implications for dating, tracing, and nuclear forensics. (15th March 2019) - Martz, Pierre; Mercadier, Julien; Perret, Julien; Villeneuve, Johan; Deloule, Etienne; Cathelineau, Michel; Quirt, David; Doney, Amber; Ledru, Patrick
Highlights: Post-crystallization interactions between uraninites and fluids can result in strong chemical (major, minor, trace element) and isotopic (U-Pb-O) heterogeneities. U-Th-Pb chemical and 207 Pb/ 206 Pb clustering ages should be used with caution as they may represent clusters of analyses of similar alteration intensity rather than distinct fluid flow events. Elements that have been considered immobile, like REEs, may in fact be significantly affected by fluid-driven post-crystallization interactions. Abstract: This study presents systematic chemical (U, Pb, Ca, Si, Fe) mapping coupled with in situ analyses of major, minor and trace elements, U/Pb, 207 Pb/ 206 Pb, and O isotopic compositions of natural uraninites (UO2 ) from two samples of the high-grade uranium ore from the Cigar Lake unconformity-related uranium deposit (Athabasca Basin, Saskatchewan, Canada). The studied uraninites are characterized by major chemical and isotopic heterogeneities expressed at small scale (µm to tens of µm), from almost pristine zones to strongly altered material. The 206 Pb/ 238 U and 207 Pb/ 235 U ratios of the different areas are widely spread and depict two similar and well-defined Discordia, providing an upper intercept age of crystallization at ca. 1300 Ma (1299 ± 4 and 1308 ± 14 Ma, respectively) and lower intercepts at 38 ± 13 and 72 ± 22 Ma, respectively. The freshest areas are characterized by sub-concordant 206 Pb/ 238 U and 207 Pb/ 235 U ratios, identical chemical compositions and similar very low δ 18 O values (−39.3 to −31.4‰). These data indicate that the two uraninites both crystallized at ca. 1300 Ma, from the same fluid and under identical physico-chemical conditions. Alteration is characterized by (i) the progressive incorporation of Ca, Si, and Fe, reaching several wt.%, which substitute to the radiogenic Pb and cause a progressive decrease in the Pb/U isotopic ratios. The radiogenic Pb is also substituted by water during the alteration, (ii) concomitant variations in trace element contents (As, Mn, V, LREEs, Sr, Th, B, Ba, Nb, for example) and (iii) heavier δ 18 O signatures (−22.5 to −8.91‰), typical of meteoric waters, in the altered zones. This combined approach demonstrates that fluid-driven post-crystallization exchanges affected each uraninite during recent fluid flow events (ca. 40 Ma and 70 Ma respectively). The relatively high dispersion of the Pb/U ratios in relation to the Discordia for both samples is considered as linked to a local (nm to µm-scale) differential mobility between lead and uranium within the uranium oxides. The chemical changes affecting elements previously considered as immobile in uraninite, such as REEs, indicate that these elements are not preserved during the post-crystallization alteration process studied here. Alteration processes may therefore have a major impact on the classical geochemical tracers, such as REE patterns or LREE/HREE ratios, currently used in nuclear forensic studies. The isotopic and chemical tracers currently used to track back the origin, age and history of natural uraninites should therefore be considered with a high degree of caution to avoid misleading and erroneous conclusions. Moreover, the comparison of calculated U-Th-Pb chemical, 207 Pb/ 206 Pb, and Pb/U isotopic ages shows that the use of age clustering for determining U-Th-Pb chemical ages and 206 Pb/ 207 Pb ages is not appropriate for constraining crystallization stage(s) of altered uraninites and for deciphering the different fluid events that potentially altered or recrystallized the uraninites over time. This study also indicates that estimation of the crystallization age of uraninite from substitution trends of Pb to Ca is not applicable to unconformity-related U deposits and results in overestimated ages because of an initial integration of calcium in the uraninite lattice at the time of crystallization.